URGENSI KEPEMIMPINAN BERINTEGRITAS PUBLIK DALAM NEGARA HUKUM DI TENGAH PANDEMI COVID-19 - Mustakim Mustakim; Herman Herman (Jurnal Ilmu dan Budaya, 2020)
Corona virus disease (Covid-19) pandemic had resulted in a deep anxiety for the whole world, including Indonesia. A number of cross sectorial effort had been conducted to overcome this disaster by the government, including in the low sector by rearranging a lot of regulation to speed up the effort on overcoming the Covid-19 Pandemic. Instead of slowing down, the spread of Covid-19 has been relatively increasing. According to the data per 18 Mei 2020 showed by BBC Indonesia, out of 18.010 cases, it is noted that the addition of the total number of the cases reached 500-600 cases per day; it was a big number compared to what happened on 200-300 cases per day. In addition, the policy of handling Covid-19 pandemic invite a lot of comments because it resulted in some problems due to the weakness of the public leader integrity. The miss-distribution of the aid, the abuses of power among special presidential officer (stafsus), and the corruption of pandemic handling budget were the empiric picture of the problems. The method of this study was juridical and comparative. This study aimed to describe the urgency to realize integrated public leadership in a law state during Covid-19 pandemic. The result of this study was one of the important factors that could influence the handling of non-natural disaster, including Covid-19 pandemic, the integrity of public leader. Public integrity is defined as honest and sincere attitudes to do what is right and fair in every situation so as to sharpen his decisions and actions within the framework of public service.